A contribution to cavernicolous beetle diversity of South China Karst: eight new genera and fourteen new species (Coleoptera: Carabidae: Trechini) - Tian, Mingyi; Huang, Sunbin; Jia, Xinyang (Zootaxa, 2023)
The specific diversity of Chinese cave fauna of the ground beetle tribe Trechini is further enriched. Eight new genera and species of trechine beetles are reported from limestone caves in southern China karsts: Youtrechus zijunae n. gen., n. sp. (Xianning, southeastern Hubei Province), Wumengius fengi n. gen., n. sp. (Liupanshui, western Guizhou Province), Chenotrechus parvulus n. gen., n. sp. (Laibin, central Guangxi Zhuang Autonomous Region), Sinaphaenopoides zhaoyiae n. gen., n. sp. (Chenzhou, southern Hunan Province), Ecotrechus ruruiae n. gen., n. sp. Hurites yunxianicus n. gen., n. sp. (Shaoyang, central Hunan Province), Pangaphaenops seraphicus n. gen., n. sp. (Bama, northwestern Guangxi Zhuang Autonomous Region) and Zunotrechus zhaojieyui n. gen., n. sp. (Zunyi, northern Guizhou Province). All the above genera are monospecific. Generic diagnosis of each new genus, with discussions on its possible phylogenetic position within the tribe Trechini, and description of the type species are provided. The following new species of cavernicolous trechines are described: Dongodytes (Dongodytodes) pingjingae sp. n. (Hechi, northern Guangxi Zhuang Autonomous Region), Dongodytes (s. str.) mingruoae n. sp. (Du’an, Hechi, northern Guangxi Zhuang Autonomous Region), Deuveaphaenops (Furongius) huangheae n. sp. (Daozhen, Zunyi, northern Guizhou Province), Shilinotrechus zhangfani n. sp. (Mile, Honghe Hani & Yi Autonomous Prefecture, southeastern Yunnan Province), Guizhaphaenops (s. str.) wanghaoi n. sp. (Qinglong, Qianxinan Buyi & Miao Autonomous Prefecture, southwestern Guizhou Province), and Graciliblemus gui n. sp. (Liping, Qiandongnan Miao & Dong Autonomous Prefecture, southeastern Guizhou Province). Further generic characteristics of the genus Graciliblemus Deuve & Tian, 2016 are added. A distribution map for all above new taxa is given.